A MASTERY LEARNING MODEL ANALYSIS IN THE CONTEXT OF 21ST-CENTURY LEARNING - nining Guspita Sari nining (CV Grasta Glory, 2026)
The mastery learning model is a teaching method that focuses on mastery of learning objectives for students before teaching them the next content. This model is related to 21st-century learning, as it requires 4C (critical thinking, creativity, communication, and collaboration) skills and caters to a range of individual learners. This article review focuses on the strengths, weaknesses, and relevance of mastery learning in the contemporary system of education. The method adopted is a methodical literature review of published scientific articles. This study concludes that mastery learning actually strengthens conceptual understanding, motivation for learning material, and academic effectiveness; however, it has time management and preparation aspect challenges for teachers. Thus, utilizing digital technologies in the classroom is one of the most effective methods of instructional teaching in the 21st-century era; as a matter of fact, Mastery Learning can play an active role in it.